2018
DOI: 10.1111/oik.05291
|View full text |Cite
|
Sign up to set email alerts
|

Developmental plasticity for male secondary sexual traits in a group of polyphenic tropical butterflies

Abstract: Many organisms alter their investment in secondary sexual traits to optimise the fitness tradeoff between reproduction and survival. Though seasonal variation in the expression of sexual traits is evident (e.g. conspicuous breeding plumage in birds), little attention has been given to short‐lived organisms that inhabit relatively stable environments throughout their own lifetime but are exposed to strong environmental variation across generations. Some insects have evolved seasonal polyphenism to cope with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…In contrast, MSP2 amount kept increasing across ages in both seasonal forms as previously observed in WS-27/27 [35]. Importantly, stable amounts of MSP2 component across developmental temperatures in our two experiments suggest that hexadecanal may matter for mating success for all males independently of their developmental history, extending the importance of the MSP2 component for mating success, which is so far established for WS-27/27 males [35,36,64,65]. Our results highlight the complexity of how sexual selection shapes the male sex pheromone composition in this polyphenic species that displays a sex role reversal across seasons [23,43].…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, MSP2 amount kept increasing across ages in both seasonal forms as previously observed in WS-27/27 [35]. Importantly, stable amounts of MSP2 component across developmental temperatures in our two experiments suggest that hexadecanal may matter for mating success for all males independently of their developmental history, extending the importance of the MSP2 component for mating success, which is so far established for WS-27/27 males [35,36,64,65]. Our results highlight the complexity of how sexual selection shapes the male sex pheromone composition in this polyphenic species that displays a sex role reversal across seasons [23,43].…”
Section: Discussionsupporting
confidence: 81%
“…Finally, lab studies have also shed light onto the genetic architecture and constraints on the evolution of thermal reaction norms (Holloway and Brakefield, 1995;Brakefield, 1996;Wijngaarden and Brakefield, 2001;Wijngaarden et al, 2002). On the other hand, field collections allowed for characterization of differences in reaction norms between geographical populations of B. anynana (de Jong et al, 2010) and between Bicyclus species (van Bergen et al, 2017;Balmer et al, 2018).…”
Section: Phenotypic Plasticity and Climate Changementioning
confidence: 99%
“…Because temperature experienced later in development should better predict the adult conditions than temperatures experienced prior to or during the previous winter, this would be surprising, although it remains possible. Additionally, in parts of the range where the flight season lasts beyond the end of summer (Paulson, , ), warmer larval temperatures could indicate that individuals will encounter cooler autumnal temperatures as adults (Prudic et al ., ; Stoehr & Wojan, ; Balmer et al ., ). Although the reproductive season concludes when it is still relatively hot for the focal population (see ‘Study Species and study overview’), the observed wing colour response could be favoured by intrasexual selection in other parts of the range, perhaps maintained by gene flow and only small thermal costs to territorial success.…”
Section: Discussionmentioning
confidence: 97%